Speed Limits: A Perspective from Behavioral Ecology - Leandro, Mauricio (2010)
The case of speeding as an unsustainable behavior facilitated by deficient design conditions is discussed. In order to include different road users in an effective, democratic way, a revision of the methods by which speed limits are calculated is also suggested. In conclusion, an ecological approach to the problem of speeding is introduced as more suitable if compared to the current rational approach.